2008
DOI: 10.1371/journal.ppat.0040029
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model for Chikungunya: Young Age and Inefficient Type-I Interferon Signaling Are Risk Factors for Severe Disease

Abstract: Chikungunya virus (CHIKV) is a re-emerging arbovirus responsible for a massive outbreak currently afflicting the Indian Ocean region and India. Infection from CHIKV typically induces a mild disease in humans, characterized by fever, myalgia, arthralgia, and rash. Cases of severe CHIKV infection involving the central nervous system (CNS) have recently been described in neonates as well as in adults with underlying conditions. The pathophysiology of CHIKV infection and the basis for disease severity are unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
604
6
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 527 publications
(679 citation statements)
references
References 42 publications
56
604
6
13
Order By: Relevance
“…From there, the virus will find its way into the blood vessels before dissemination to the target tissues/or organs (17). Although the exact route and mechanisms of early infection is poorly defined (18), previous studies from other alphaviruses have indicated the involvement of different immune cell populations in the skin (19)(20)(21)(22), and migrating cells such as macrophages and/or dendritic cells (DCs) (19). The events taking place during the acute blood phase of CHIKV infections have not been clearly defined.…”
Section: Hikungunya Virus (Chikv) Is the Causative Agent Formentioning
confidence: 99%
“…From there, the virus will find its way into the blood vessels before dissemination to the target tissues/or organs (17). Although the exact route and mechanisms of early infection is poorly defined (18), previous studies from other alphaviruses have indicated the involvement of different immune cell populations in the skin (19)(20)(21)(22), and migrating cells such as macrophages and/or dendritic cells (DCs) (19). The events taking place during the acute blood phase of CHIKV infections have not been clearly defined.…”
Section: Hikungunya Virus (Chikv) Is the Causative Agent Formentioning
confidence: 99%
“…As mother-to-child transmission is rare in antepartum but frequent in the context of intrapartum maternal viremia, and the placenta is not a site of viral replication, this favors a model of vertical transmission via placental breaches that forms around the term during parturition, as described for a number of other viruses associated with elevated maternal viremia during delivery, such as HIV, HBV, and arboviruses such as Dengue virus or West Nile virus (Couderc et al 2008;Gerardin et al 2008).…”
Section: Microbes and The Placental Barriermentioning
confidence: 99%
“…Neonatal mice and mice deficient in the type I interferon receptor were found to be highly susceptible to CHIKV infection. 19 Although CHIKV was detected in muscle and joint tissue in these mice, the pathological outcomes in these tissues were not addressed, 19 and these models may be more relevant for studying the pathogenesis of atypical CHIKV disease. Ziegler et al 20 described severe skeletal muscle necrosis and inflammation after CHIKV infection of outbred strains of mice.…”
mentioning
confidence: 99%